EVALUASI PENERAPAN SANITASI DI TERMINAL ALAM BARAJO, KOTA JAMBI - Elma Mutmainnah; Zuli Rodhiyah; Putri Ayu Ramadhani; Muhammad Fadly (Lingkar: Journal of Environmental Engineering, 2023)
Terminal Alam Barajo is a one of the public places used to manage arrivals and departures, raise and drop off people and/or goods, as well as transfer modes of transportation. Access to the Terminal Alam Barajo is quite easy because it is located in Jambi City. Terminal Alam Barajo location requires management support and sanitation facilities that support the creation of healthy station. This research was conducted to assess the application of sanitation at the Terminal Alam Barajo, Jambi City. This research was conducted using a combination of qualitative methods in the form of observation and interviews. The sanitation assessment is carried out using an environmental health inspection assessment. While sanitation information obtained from in-depth interviews with chief cleaning officer terminal Alam Barajo. The sanitation assessment of the Terminal Alam Barajo obtained a score 88% of environmental component, 73% of Sanitation Facilities component, 75% of other components. Sanitation at the Terminal Alam Barajo is deemed healthy because the overall score of the variables is above 79% but still needs further improvement in sanitation.